2018
DOI: 10.1038/s41598-018-32918-w
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Synthesis of Luminescent Hemoglobin Capped Hollow Porous Platinum Nanoclusters and their Application to Catalytic Oxygen Reduction and Cancer Imaging

Abstract: Engineering hollow and porous platinum nanostructures using biomolecular templates is currently a significant focus for the enhancement of their facet-dependent optical, electronic, and electrocatalytic properties. However, remains a formidable challenge due to lack of appropriate biomolecules to have a structure-function relationship with nanocrystal facet development. Herein, human hemoglobin found to have facet-binding abilities that can control the morphology and optical properties of the platinum nanoclus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Therefore, it would be an easy method of identifying Escherichia coli strains in a rapid and effective manner even at a low Escherichia coli concentration of only 8.3 × 103 CFU/mL. The Hb-FeQCs are also water-soluble, stable, biocompatible, and highly sensitive to bacterial concentrations, especially in the urine medium [ 193 , 194 , 195 ].…”
Section: Nanotechnology Used As a Diagnostic Methods And In Antimicro...mentioning
confidence: 99%
“…Therefore, it would be an easy method of identifying Escherichia coli strains in a rapid and effective manner even at a low Escherichia coli concentration of only 8.3 × 103 CFU/mL. The Hb-FeQCs are also water-soluble, stable, biocompatible, and highly sensitive to bacterial concentrations, especially in the urine medium [ 193 , 194 , 195 ].…”
Section: Nanotechnology Used As a Diagnostic Methods And In Antimicro...mentioning
confidence: 99%
“…19 Bipyridine-Pt( ii )-alkynyl complexes with AIPE behavior can show decent EL performances with a maximal external quantum efficiency ( η ext ) of 5.8% and a current efficiency ( η L ) of 18.4 cd A −1 , 20 while Pt( ii ) diimine acetylide complexes with good AIPE nature can act as effective optical power limiters. 21–23 Recently, AIPE behaviors have been found in Pt II (C^N)(N-donor ligand)Cl-type complexes to show great potential in mesoporous emissive materials, 24 cell labels, 25 high performance OLEDs 26 etc . Importantly, it has been found that AIPE-active Pt II (C^N)(N-donor ligand)Cl-type complexes involve a new AIE mechanism called restrained D 2d deformation of the coordinating skeleton of these complexes from square-planar ( D 4h ) in the ground states to a tetrahedral ( T d ) skeleton in the excited states.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin (Hb) is one of the main components of red blood cells and is characterized as iron-rich, and it can reversibly combine oxygen molecules and release the molecules into tissues according to the oxygen level . Over the past decades, Hb-based oxygen carriers (HBOCs) have gained widespread attention, , and various types of HBOC have been developed, such as glutaraldehyde-polymerized Hb and polyethylene glycol-conjugated Hb (PEG-Hb). , Herein, we designed an artificial oxygen carrier system, a Hb loaded liposome (Hb@lipo), which presented a stable Hb encapsulation and high oxygen binding ability. Moreover, we developed a liposome containing cabazitaxel (CBZ@lipo), a chemotherapeutic agent belonging to the taxane class.…”
Section: Introductionmentioning
confidence: 99%